Risk perceptions, knowledge and protection practices related to COVID-19 in Dessie City Administration, Northeast Ethiopia: a community-based study - Husien Nurahmed Toleha; Ewunetie Mekashaw Bayked; Birhanu Demeke Workneh; Teferi Gedif Fenta (Frontiers in Public Health)
BackgroundCOVID-19 is a global concern due to its high transmission and mortality rates. Despite governments’ efforts worldwide to control its spread, many people were hesitant to adopt preventive measures. The effectiveness of these measures largely depends on public willingness, which is influenced by their knowledge and perception of risk. Therefore, this study aimed to examine the knowledge, risk perceptions, protection practices, and related factors concerning COVID-19 in the Dessie City Administration, Northeast Ethiopia.MethodologyThis study employed a cross-sectional design. We selected seven hundred ninety participants using a systematic sampling technique. Data was collected face-to-face using an interviewer-administered questionnaire. Descriptive statistics, including frequency, percentage, mean, and standard deviation, were used to summarise the sample characteristics. Multivariable logistic regression analysis was conducted using SPSS (version 23), and the results were presented in the form of text, tables, and graphs.ResultsOf the study participants, 498 (63%) had good knowledge of the pandemic, while 457 (58%) had a low-risk perception. Only 305 (39%) demonstrated good protection practices. The most trusted sources of information were healthcare personnel (686 participants, 86.8%), followed by the Ministry of Health websites (654 participants, 82.8%). Monthly income (>10,000 ETB), knowledge, and risk perceptions with AORs of 3.05 (CI: 1.51–6.14), 4.45 (CI: 2.81–7.04), 2.06 (CI: 1.38–3.08) were significantly associated with protection practices against the COVID-19 pandemic.ConclusionMore than two-thirds of the participants demonstrated good knowledge about COVID-19. However, over half perceived themselves to be at low risk and engaged in poor preventive practices. Control efforts will be challenging, especially among younger and less educated groups who consider themselves at low risk, requiring focused attention. Understanding people’s risk perceptions and beliefs about the effectiveness of COVID-19 prevention measures is essential for improving protective behaviours. Health education and active community engagement are key strategies in combating the spread of the virus.